The Impact of Computer-Assisted Instruction on Student Performance: Evidence from the Dual-Teacher Program - Haizheng Li; Zhiqiang Liu; Fanzheng Yang; Li Yu (Institute of Labor Economics (IZA), 2023)
We present findings from an evaluation study of the Dual-Teacher program, a computer- assisted instruction program, that makes lecture videos and other teaching resources from an elite urban middle school available through the internet to schools in poor and remote areas in China. The unique design of the study allows us to not just estimate the effect of the program on student performance but distinguish the direct effect coming from students' exposure to the lecture videos in class and the indirect effect due to improved instruction quality of the local teacher who uses the lecture videos in lesson preparation. Using the difference-in-differences method, we find that the Dual-Teacher program improves student performance in math by 0.978 standard deviations over the three-year middle school education, of which 0.343 standard deviations are attributable to the indirect effect. We also find that the positive impacts of the program are cumulative and robust to student and teacher characteristics as well as a plethora of other considerations. From a policy perspective, our findings suggest that the Dual-Teacher program is an effective and low cost means to improve education outcomes in underserved areas and hence help close cross-region gaps in education.
Keywords: I21; I24; I28; O15; 330; computer-assisted instruction; computer-assisted learning; education policy; inequality